1866 Ga. Laws 27-28 - (:unkn) unknown (My University, 1866)
An Act to Authorize the Justices of the Inferior Courts of Camden, Glynn and Effingham Counties to Levy a Special Tax for County Purposes, and to regulate the same, §§ 3-4: Allowed these three counties to collect a tax of one dollar per gun or pistol, musket, or rifle over the number of three owned or kept on any plantation.
Keywords: TAX - PROPERTY OR SALES